The Genetics of Deafness in Domestic Animals - Strain, George M. (Frontiers in Veterinary Science, 2015)
Although deafness can be acquired throughout an animal’s life from a variety of causes, hereditary deafness, especially congenital hereditary deafness, is a significant problem in several species. Extensive reviews exist of the genetics of deafness in humans and mice, but not for deafness in domestic animals. Hereditary deafness in many species and breeds is associated with loci for white pigmentation, where the cochlear pathology is cochleo-sacular. In other cases there is no pigmentation association and the cochlear pathology is neuroepithelial. Late onset hereditary deafness has recently been identified in dogs and may be present but not yet recognized in other species. Few genes responsible for deafness have been identified in animals, but progress has been made for identifying genes responsible for the associated pigmentation phenotypes. Across species, the genes identified with deafness or white pigmentation patterns include MITF, PMEL, KIT, EDNRB, CDH23, TYR, and TRPM1 in dog, cat, horse, cow, pig, sheep, ferret, mink, camelid, and rabbit. Multiple causative genes are present in some species. Significant work remains in many cases to identify specific chromosomal deafness genes so that DNA testing can be used to identify carriers of the mutated genes and thereby reduce deafness prevalence.